PENGARUH PEMBERIAN ETHEPON TERHADAP PRODUKSI TANAMAN KEDELAI (GLYCINE MAX L. MERRIL) PADA JARAK TANAM BERBEDA - Ninda Sophia Abrina Sitorus; Aslim Rasyad; Nurbaiti ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Application of ethepon on soybean grown under densely population is expected to enhance plant growth and increase assimilate translocation to seed. Ethrel 40 PGR is chemical compound containing ethepon, when it is in plant organ would be converted to ethylene and may accelerate flowering. This study aims to determine the effect of ethepon on soybean crop production under two different planting spaces. A field experiment was conducted by using split plot design, in which four levels of ethepon concentration ie; 100 ppm, 200 ppm, 300 ppm, and control were assigned to main plot and two levels of planting spaces ie; 40 cm x 15 cm and 40 cm x 20 cm were assigned as subplot. Traits observed were plant height, days to flower, days to harvest, filled pod numbers per plant, seeds number per plant, grain yield m² and 100-seed weight. The results showed that applicqation of ethepon shorten plant height, accelerate day to flowering faster but delay harvesting time at planting space of 40 cm x 15 cm and 40 cm x 20 cm. Yield components such as number of filled pods per plant and grain yiel per unit area were lower due to application of ethepon for both planting spaces. The implication drawn from this research was that application of ethepon could not be recommended for soybean. Keywords: soybean, ethepon, planting spaces and production.